Compression of satellite data - Barrio, Roberto; Elipe, Antonio (Revista Matemática Complutense, 2002)
In this paper, we present the simple and double compression algorithms with an error control for compressing satellite data corresponding to several revolutions. The compressions are performed by means of approximations in the norm L1 by nite series of Chebyshev polynomials, with their known properties of fast eval-uation, uniform distribution of the error, and validity over large intervals of time. By using the error control here introduced, the number of terms of the series is given automatically for a prede-termined tolerance. As illustration, we apply the method to the orbits of SPOT, Topex/Poseidon and Skybridge satellites.